2022
DOI: 10.14309/ajg.0000000000001795
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Biologics for Endoscopic Healing of the Ileum and Colon in Crohn's Disease

Abstract: INTRODUCTION: We compared the efficacy of adalimumab, infliximab, ustekinumab, and vedolizumab on the ability to achieve endoscopic healing (EH) after 1 year of therapy in moderate-severe Crohn's disease (CD). METHODS:This was a pooled analysis of patient-level data from 299 patients with CD from 4 clinical trials.Proportions of patients treated with each biologic were compared for achieving 1-year complete EH (Simple Endoscopic Score for CD [SES-CD] <3) and ileal and colonic EH separately (SES-CD 5 0). Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Our finding that adalimumab-treated patients incurred lower CD-related HRU compared to vedolizumab-treated patients is consistent with the findings reported in existing literature, and may be partially attributable to the superiority of anti-TNFs versus α 4 β 7 integrin blockers in healing small bowel for patients with CD. 35 Despite both adalimumab and vedolizumab effectively leading to endoscopic remissions in moderate-to-severe inflammatory bowel disease (IBD), different findings have been reported in CD versus UC. The VARSITY trial 23 showed superiority of vedolizumab over adalimumab in UC regarding endoscopic improvement at week 52.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that adalimumab-treated patients incurred lower CD-related HRU compared to vedolizumab-treated patients is consistent with the findings reported in existing literature, and may be partially attributable to the superiority of anti-TNFs versus α 4 β 7 integrin blockers in healing small bowel for patients with CD. 35 Despite both adalimumab and vedolizumab effectively leading to endoscopic remissions in moderate-to-severe inflammatory bowel disease (IBD), different findings have been reported in CD versus UC. The VARSITY trial 23 showed superiority of vedolizumab over adalimumab in UC regarding endoscopic improvement at week 52.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a 2022 post-hoc analysis of pooled data from patients with moderate-to-severe CD from four clinical trials reported superior rates of one-year endoscopic healing in adalimumab-treated and infliximab-treated patients than vedolizumab-treated patients. 35 …”
Section: Discussionmentioning
confidence: 99%
“…We observed class membership to be associated with early biologic treatment. It is arguably reasonable to expect an association between biologic treatments and FCAL profiles given the often-reported association between FCAL and endoscopic activity and an association between biologic treatments and endoscopic healing for CD patients 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Narula et al [21] recently performed a post hoc analysis of pooled participant-level data from several clinical trials of biologics in patients with moderate to severe CD. Overall, ileal and colonic endoscopic healing were separately assessed using each segment score of the SES-CD.…”
Section: Difference In Endoscopic Healing Between the Small Bowel And...mentioning
confidence: 99%